Genome-Wide Screening for Novel Candidate Virulence Related Response Regulator Genes in Xanthomonas oryzae pv. oryzicola - Zhang, Zheng-Chun; Zhao, Min; Xu, Li-Dan; Niu, Xiang-Na; Qin, Hong-Ping; Li, Yi-Ming; Li, Mei-Lin; Jiang, Zhong-Wei; Yang, Xia; Huang, Guang-Hui; Jiang, Wei; Tang, Ji-Liang; et al. (Frontiers in Microbiology, 2018)
Two-component regulatory system (TCS), a major type of cellular signal transduction system, is widely used by bacteria to adapt to different conditions and to colonize certain ecological niches in response to environmental stimuli. TCSs are of distinct functional diversity, genetic diversity, and species specificity (pathovar specificity, even strain specificity) across bacterial groups. Although TCSs have been demonstrated to be crucial to the virulence of Xanthomonas, only a few researches have been reported about the studies of TCSs in Xanthomonas oryzae pathovar oryzicola (hereafter Xoc), the pathogen of rice bacterial streak disease. In the genome of Xoc strain GX01, it has been annotated 110 TCSs genes encoding 54 response regulators (RRs), 36 orthodox histidine kinase (HKs) and 20 hybrid histidine kinase (HyHKs). To evaluate the involvement of TCSs in the stress adaptation and virulence of Xoc, we mutated 50 annotated RR genes in Xoc GX01 by homologous vector integration mutagenesis and assessed their phenotypes in given conditions and tested their virulence on host rice. 17 RR genes were identified to be likely involved in virulence of Xoc, of which 10 RR genes are novel virulence genes in Xanthomonas, including three novel virulence genes for bacteria. Of the novel candidate virulence genes, some of which may be involved in the general stress adaptation, exopolysaccharide production, extracellular protease secretion and swarming motility of Xoc. Our results will facilitate further studies on revealing the biological functions of TCS genes in this phytopathogenic bacterium.